Influence of Electronic Word-of-Mouth on Destination Image of Chinese Tourists Travelling to Phuket - Wu, Yujie (Prince of Songkla University, 2022)
Thesis (M.B.A., Hospitality and Tourism Management (International program))--Prince of Songkla University, 2021